An observational study to evaluate the outcome of patients admitted in pediatric intensive care unit (PICU) using pediatric risk of mortality (PRISM-III) score in a tertiary care hospital of West Bengal - Sudipto Paul,; Kanai Lal Barik,; Nilanjan Ghosh,; Laha, Sumanta; Sayan Bera,; Sukanya Nath, (Asian Journal of Medical Sciences, 2023)
Background: Pediatric risk of mortality (PRISM III) score is used across the globe to predict the mortality of hospitalized children by an objective method based on 17 variables measured during first 24 h of admission in pediatric intensive care unit (PICU). Aims and Objectives: We have done this study to evaluate the cause, management and outcome of PICU admissions and also to find out the statistical significance of PRISM III score in predicting mortality. Materials and Methods: This observational prospective study was conducted for a period of 1 year in the PICU of a district Medical College of West Bengal among children 1–12 years age. They were divided into 4 groups according to the PRISM III scores of 1–10, 11–20, 21–30, and >30 and outcome in all the groups were recorded and analyzed. Results: Respiratory (25%), neurological (20.1%), and infectious (17.3%) etiology were major cause of PICU admission. About 17.4% patients needed mechanical ventilation, 31.2% Continuous Positive Airway Pressure and 66% patients inotropic support. Out of 144 cases, 117 discharged and 27 expired. Percentage of death is 100%, 44.4%, 21.6%, and 4.6% among child with PRISM III score of >30, 21–30, 11–21, and ≤10, respectively. Significant increase in mortality noted with increase in number of organ failures. Specificity and positive predictive value increases with higher PRISM III score and sensitivity and negative predictive value is more with low PRISM III score. Conclusion: PRISM III score can be used as a triage tool in limited resource settings for early initiation of intense management to high risk and salvageable cases.